Highly hydrophobic metal–organic framework for self-protecting gate dielectrics. Issue 24 (22nd April 2020) - Inamdar, Arif I.; Pathak, Abhishek; Usman, Muhammad; Chiou, Kuan-Ru; Tsai, Pei-Hsien; Mendiratta, Shruti; Kamal, Saqib; Liu, Yen-Hsiang; Chen, Jenq-Wei; Chiang, Ming-Hsi; Lu, Kuang-Lieh
Abstract : A high- κ copper-based metal–organic framework with unusual dielectric behaviour and outstanding water resistant properties was successfully designed for self-protecting microelectronic devices as gate dielectrics. Abstract : A hydrophobic metal–organic framework (MOF) showing high- κ behaviour was synthesized by the reaction of copper ions with 4, 4′-(hexafluoroisopropylidene)diphthalic anhydride (HFDPA ). The unique, highly hydrophobic nature of the material protects it from re-adsorbing water, even in a high humidity environment. The dielectric constant of the MOF showed an unprecedented increasing trend, reaching up to κ ≈ 99 at 300 K and 1 kHz after the complete removal of guest and coordinated water molecules. The unusual dielectric behaviour of the compound along with its water resistant properties is the first report of such behaviour and it paves the way for the development of moisture-stable microelectronic devices.